The Sound and the Fusae: Music Notation as a Means of Time Travel (Undergraduate Research Journal; 2017, 2017)
The Renaissance composer Crispinus van Stappen was born during a time in which luxuries such as cloud storage and back-up files had yet to be invented; if something went missing, it stayed that way. Unfortunately, this happened with one of the voices to his five-voice motet Exaudi nos filia . Without this voice his composition is incomplete and unperformable. If one wanted to complete van Stappen's composition and recreate this missing voice, what would one have to take into consideration to get the most accurate result without creating a time machine, traveling back in time, and listening to the original? I propose to recreate the missing voice to Exaudi nos filia using the original white mensural system of notation, exploring the possibilities that this approach has for historically accurate composition and how the system itself could influence me as a composer when recreating this voice. Composing any piece of music requires the melding of sound and symbol: music theory and analysis take care of the sound and notation takes care of the symbol. With analyzing, transcribing, performing, and listening to contemporaneous pieces one can gain an aural feel for the aesthetic of the music. Likewise, studying the music theory of the era can provide one with the guidelines and rules that composers of that time would have followed. This lays out a map of what procedures were common and what the people of that era were used to hearing. However, theory and intent listening can only provide so much information to a modern ear trained in a modern setting. White mensural notation is a close precursor to our modern notational system and while the similarities between them are enough to render it readable with practice, there are key differences that create an unfamiliar atmosphere for writing music. Modern instruments can play early music, but performing on period instruments allows performers to momentarily time travel and gain the motions naturally existent in the instruments of that era, creating an entirely different sound and gestural vocabulary. Just as playing on period instruments creates a different performance perhaps writing in a period notation, where stylistic elements can happen naturally due to the system, can also create a different composition.
Keywords: Notation; Early Music; Period Composition